Psychopathology and Anxiety Outcomes in Female Anorexic Exercisers and Nonexercisers - Kuhnle, Megan C. (Tufts Archival Research Center, 2019)
Anorexia nervosa (AN) is a serious eating disorder that causes extreme weight loss and has severe physical and psychological ramifications. It is more prevalent among females than males and 1.2% of females in the United States will be diagnosed with AN at some point in their lifetime. AN is often seen with depression and anxiety as comorbidities and has the highest mortality of any psychological disorder. Excessive exercise is frequently implicated as part of an AN diagnosis therefore understanding the role exercise plays in the psychopathology and anxiety outcomes of AN patients is essential in order to optimize treatment strategies and understand the best way to incorporate exercise as part of recovery. Data were analyzed from four studies conducted in the Neuroendocrine Unit at Massachusetts General Hospital to better understand the relationship between exercise and eating disorder psychopathology and anxiety outcomes among anorexic exercisers and nonexercisers. No significant difference was found in eating disorder psychopathology as measured by the Eating Disorders Examination Questionnaire (EDE-Q) between exercisers and nonexercisers. Among exercisers, the number of hours per week exercised was significantly positively (p<0.05) related to an higher eating disorder psychopathology scores (EDE-Q). Exercisers were found to have significantly lower anxiety levels as measured by the Spielberger State-Trait Anxiety Inventory (STAI-Trait) compared to nonexercisers (p<0.05). The results of this study indicate that exercise is an important factor to consider when evaluating the mental health of patients with AN and should be further examined to determine appropriate recommendations for exercise regimens during treatment for AN.